Glycated haemoglobin acts as an indicator of dislipidemia in patients with Type II diabetes mellitus - Sahrin, Sumaia; Jharna, Dilruba Easmin; Khan, M Shafiqul Islam; Debnath, Jayati; Talukder, Suman (Research in Agriculture Livestock and Fisheries, 2018)
Diabetic patients with associated dyslipidemia are easy targets for cardiovascular diseases (CVD). Glycated hemoglobin predicts the risk for the development of diabetic complications. This study was an attempt to determine lipid abnormalities associated with Type-2 Diabetes Mellitus and association between glycated hemoglobin (HbA1c) levels and serum lipid profile to assess the importance of HbA1c as an indicator of dyslipidemia and future risk of cardiovascular disease in Bhola District, Barisal. In this cross-sectional study, 200 known patients of Type-2 Diabetes Mellitus within 35-85 years of age were randomly selected. They were investigated for HbA1c and lipid profile. The data were evaluated by Statistical Package for Social Sciences (SPSS) 16.0 version software. Independent samples t-test (2-tailed) was used to compare means of anthropometric, clinical and laboratory parameters and the effect of the glycemic control on their lipid profile was determined using correlation coefficient. Amongst the study group, 65% patients showed poor glycemic control, 35% with good glycemic control and 59.60% patient’s haddyslipidemia.HbA1c was found to have significant positive correlation with total cholesterol (TCHO), low density lipoprotein (LDL-C) and triglycerides (TG) and significant negative correlation with high density lipoprotein (HDL-C). The mean value of TC, LDL-C and TG was found to be lower in patients with good glycemic control than those with poor glycemic control. These differences were significant at the level of P<0.05. These findings conclude that the glycemic control of the patient has got a strong impact on the serum lipid level and dyslipidemia is frequently encountered in those who have got poor glycemic control. Res. Agric., Livest. Fish.5(2): 185-192, August 2018